ANALISIS IMPLEMENTASI SISTEM KEUANGAN DESA, PARTISIPASI MASYARAKAT, PERSEPSI DAN KOMPETENSI APARATUR DESA TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA STUDI KASUS PADA 16 DESA DI KECAMATAN BLORA, KABUPATEN BLORA - Rizky Putri S; Khoirul Fuad (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2025)
This research aims to determine the effect of the village financial system, community participation, perceptions and the competence of village officials on the accountability of village fund management at 16 villages in Blora District, Blora Regency. The method applied in this research is quantitative research. The data used comes from primary data obtained through distributing questionnaires using a linear scale. The technique applied in this research is purposive sampling technique. The research sample included 16 villages in Blora Subdistrict, Blora Regency with each village having 5 respondents with a total of 80 respondents. Data processing was done by multiple linear regression analysis using SPSS software. The results of this study indicate that the village financial system, community participation, and perceptions of village officials have a positive effect on the accountability of village fund management, while the competence of village officials has no effect on the accountability of village fund management.